Diseño de un plan de mantenimiento preventivo para máquina de lavado de canastillas reutilizables en cadena de suministro de alimentos para la empresa IFCO. (2025)
In this research project, a preventive maintenance plan was designed for the Brüel washing machine of the company IFCO, which is located in the warehouse of said company on the Siberia-Cota road. The knowledge acquired during the course of the mechanical engineering degree at the University of America provided the necessary bases to propose, develop and structure a preventive maintenance plan to be executed over the course of a year. Thanks to this, the company will be able to plan activities on the main components of the Brüel machine, before a breakdown or failure occurs on them, collaborating with the reduction of costs and non-operating times.